KAPITA SELEKTA ASURANSI SYARIAH: TELAAH UMUM TENTANG ASURANSI SYARIAH DI INDONESIA - A.M. Hasan Ali (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2011)
The discoures of Islamic insurance can be studied in ijtihâdî ways. Some scolars could receive insurance practice as long as it does not contradict with Islamic values. The acceptence of Islamic insurance for ulamas comes from mutual agreement institution (ijmâ‘ jamâ’î), such as Fatwa Comission of Indonesia Ulama Council (MUI) or Bahtsul Masa’il Council of Nahdlatul Ulama, and Tarjih Muhammadiyah Council. In 2001, MUI through National Sharia Council (DSN), has issued a fatwa on the general guidelines for takâful, as an initial guide operational takâful industry in Indonesia.DOI: 10.15408/aiq.v3i1.2496